ANALISIS KEPATUHAN MASYARAKAT PADA KETENTUAN BERLALU LINTAS BAGI PENGENDARA BERMOTOR RODA DUA: (Studi Kasus Pengendara Pelajar SMP di Kota Samarinda) - Apriani, Fajar; Pratiwi Fatmala, Andi Nur; Karmilasari, Vina; Rahma, Ukik Aisya (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
This study aims to determine the compliance of motor vehicle motorists who are Junior High School students in Samarinda City and its inhibiting factors. This study uses descriptive types with qualitative methods, by determining the research locations in two State Junior High Schools and one private Madrasah Tsanawiyah in the suburbs of Samarinda which based on observations is known to have many students who drive two-wheeled motorized vehicles. Primary data were obtained from interviews with key informants the Head of the Road Traffic and Head of the Safety Division of the Samarinda City Transportation Agency, Officers of the Samarinda Resort Police Traffic Law Enforcement Unit and interviews with informants from the Trustees of Intra School Student Organizations, Deputy Principal of Public Relations Division and Deputy Principal of Curriculum, as well as the owner or provider or parking lots around the scholl which is the research location. Secondary data sources include regulations regarding the provisions of traffic and field documentation. The data analysis used is combination of content analysis and interactive model analysis. The results of research that rely on data collection techniques through intensive observations, interviews and documentation showed that efforts to increase public compliance with traffic provisions including students of two-wheeled motorized vehicle drivers in Samarinda City, need to be handled not only in nature, but also require awareness and responsibility of all residents of Samarinda City. Self-awareness of each individual can arise if there is sufficient education to form knowledge, understanding and which then has an impact on changes in behavior towards orderly traffic in the public interest as an effort to build and realize the culture of security and traffic safety. The clarity of policy content requires the commitment of policy implementation apparatus in law enforcement to optimize the obedience of the target group.